The importance of remote learning: A report from the Mato Grosso State University (Research, Society and Development, 2020)
Emergency measures to contain the advancement of COVID-19 in Brazil were adopted in order to minimize the effects of the pandemic in higher education institutions. Continuing education through online courses in asynchronous mode is one of the possibilities of teaching in times of social isolation. In this movement, the present study aimed to analyze and discuss the assumptions of remote learning, based on data obtained in the asynchronous course offered by the Mato Grosso State University. We present the principles of interactive and meaningful learning, coupled with the data obtained when registering participants, comparing the scope of the remote and face-to-face course, in addition to the main reasons why participants enrolled in the courses. We emphasize that, in the virtual modality, the external communities and professionals in the area were awarded a course that did not require the face-to-face meetings from the participants, and thus, expanded the possibilities of intersection between all participants of the course, aiming at the construction of social concepts and practices. allied to the context of the professionals' performance. In addition, the quantitative data corroborated with our theoretical assumptions, as they demonstrated participation by several states of the federation, which in the face-to-face modality, would hardly have the possibility of being included in the course.